The Philosophical Salon: Speculations, Reflections, Interventions - Marder, Michael; Vieira, Patricia (Critical Climate Change, 2017)
Through the interpretative lens of today's leading thinkers, The Philosophical Salon illuminates the persistent intellectual queries and the most disquieting concerns of our actuality. Across its three main divisions-Speculations, Reflections, and Interventions-the volume constructs a complex mirror, in which our age might be able to recognize itself with all its imperfections, shadowy spots, even threatening abysses and latent promises. On the cutting edge of philosophy, political and literary theory, and aesthetics, this book courageously tackles a wide array of topics, including climate change, the role of technology, reproductive rights, the problem of refugees, the task of the university, political extremism, embodiment, utopia, food ethics, and sexual identity. It is an enduring record of an ongoing conversation, as well as a building block for any attempt to make sense of our world's multifaceted realities. Contributors: Robert Albritton, Linda Martín Alcoff, Claudia Baracchi, Geoffrey Bennington, Jay M. Bernstein, Costica Bradatan, Jill Casid, David Castillo, Antonio Cerella, Anna Charlton, Claire Colebrook, Sarah Conly, Nikita Dhawan, William Egginton, Roberto Esposito, Mihail Evans, Gary Francione, Luis Garagalza, Michael Gillespie, Michael Hauskeller, Ágnes Heller, Daniel Innerarity, Jacob Kiernan, Julia Kristeva, Daniel Kunitz, Susanna Lindberg, Jeff Love, Michael Marder, Todd May, Michael Meng, John Milbank, Warren Montag, T. M. Murray, Jean-Luc Nancy, Kelly Oliver, Adrian Pabst, Martha Patterson, Richard Polt, Gabriel Rockhill, Hasana Sharp, Doris Sommer, Gayatri Spivak, Kara Thompson, Patrícia Vieira, Slavoj Žižek.